STANDARISASI BENTUK PRODUK HUKUM SEBAGAI TINDAK LANJUT PUTUSAN MAHKAMAH KONSTITUSI PADA PERKARA PENGUJIAN UNDANG-UNDANG OMNIBUS: Standardisasi Regulasi Tindak Lanjut Putusan Mahkamah Konstitusi pada Perkara Pengujian Undang-Undang Omnibus - Jufri, Muwaffiq; Fahmi, Agung Ali; Aidonojie, Paul Atagamen; Asyiqoh, Lin; Ikubanni, Oluwaseye Oluwayomi (Jurnal Konstitusi, 2024)
The re-examination of the Job Creation Law in 2023 highlights a serious issue in the national legislative system, specifically the follow-up to the Constitutional Court’s (MK) decisions in judicial review cases (PUU) concerning the Omnibus Law. The urgency of this research stems from the high demand among lawmakers for drafting laws in the omnibus format and the potential for judicial review of such laws. This research contributes to addressing the follow-up to the Constitutional Court’s decisions by focusing on the choice of legislative forms as a response to these rulings. The research employs normative legal methods with conceptual, legislative, and case-based approaches. The findings emphasize the need to standardise the type of regulation to ensure the executability of the Constitutional Court’s decisions. The ideal regulatory form for implementing the Court’s rulings on the Omnibus Law is a law. Therefore, it is necessary to legitimise the use of laws as the standard form of follow-up to the Constitutional Court’s decisions on the Omnibus Law to maximise the executability of these rulings.